Postural Control Follows a Bi-Phasic Alteration Pattern During Mountain Ultra-Marathon - Degache, Francis; Serain, Emilie; Vernillo, Gianluca; Meyer, Frederic; Falbriard, Mathieu; Savoldelli, Aldo; Guex, Kenny; Millet, Grégoire P. (Frontiers in Physiology, 2019)
It is well knows that postural control (PC) is deteriorated with neuromuscular fatigue, altitude or sleep deprivation induced by a mountain ultra-marathon (MUM). Several regulatory mechanisms have also been reported during this type of event and the changes in PC at different points of MUM remain unknown. The purpose of this study was to investigate the time course of PC during an extreme MUM. We tested the hypothesis that PC alteration would not increase linearly. Method: 16 participants (age 45.1±9.6 yr) were tested bipedaly on a posturographic platform for 51.2s with eyes open every 50 km. Both traditional and stabilogramm diffusion analyses (SDA) were performed. A visual analog scale (VAS) was used for a subjective evaluation of global fatigue, sleep feeling and pain. Results: The main parameters (center of pressure trajectory analysis) increased significantly (p<0.001, d= 1.56, very large) until km 100. This was confirmed by SDA in the antero-posterior plane. Short term effective diffusion coefficient significantly increased (p<0.001, d=1.07, very large) as critical point (p<0.01, d=1.57, very large). From km 100 to 200, a different response was observed with a continuous decrease in most of the PC parameters. This was confirmed by SDA in the antero-posterior plane. Short term effective diffusion coefficient significantly increased (p<0.001, d=1.39, very large) as critical point (p<0.01, d=1.51, very large). Conclusion: Posture alteration is progressively increased until 100 km. After this point, compensatory mechanisms appear to limit the posture degradation. This bi-phasic response is of interest for better understanding the coping with extreme fatigue.